Critical Discourse Analysis on Medan Newspapers’ Editorial - tampubolon, sahlan (The Explora, 2023)
The aim of this paper is to explore how critical discourse analysis is realized in editorial local newspaper in Medan. The analysis is grounded based on Norman Fairclough’s assumption on critical discourse analysis that discussed three dimensions of analysis, such as micro, macro and meso. The data collected were the editorials of Medan local newspaper between June till December 2012, they are the editorial of Analisa, Andalas, Medan Bisnis, Orbit, Sinar Indonesia Baru (SIB), Waspada that observed three major topic of discussions like topic on politics, state officials, and social phenomena. Findings are in micro analysis includes language use such as the realization of genre, passive voice, collective noun and naming individual, in macro-analysis shows that the editorials position to control, and in meso analysis are the editorial’s role in giving his thought. These findings shows that the Medan local newspaper have just enjoyed for free press in delivering the news. Key words: Micro, macro, meso analysis.